1997
DOI: 10.1177/002199839703100402
|View full text |Cite
|
Sign up to set email alerts
|

Damage Detection by Piezoelectric Patches in a Free Vibration Method

Abstract: An experimental program was undertaken to evaluate the feasibility of using piezoelectric patches for damage detection in composite materials. The fact that damage development can cause shifts in the natural frequencies of a structural component suggested an impulse-frequency response approach, in which free vibration was initiated by a single external mechanical pulse and was sensed by piezoelectric patches. Patches in both surface-bonded and embedded configurations were tried. The investigation was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Examples include aerospace/aircraft structures [27,28], robot manipulators [29], vibration controls and isolations, high-precision devices, microsensors/actuators, thin-film MEMS [30], health monitoring [31], microdisplacement actuation and control [25], and so on. Additional applications in smart structures and structronic systems encompass distributed structural control [16,[32][33][34][35][36], rotor dynamics control [37], self-sensing actuators [38][39][40], orthogonal modal sensors/actuators [41][42][43], space truss members [44], noise control [45], vibration isolators [46], active constrained damping [47], morphing of wings and blades [48], microscopic neural-sensing and actuation characteristics of conical, paraboloidal, toroidal and spherical structronic shells [49][50][51][52][53][54][55], and so on.…”
Section: Piezoelectric Materialsmentioning
confidence: 99%
“…Examples include aerospace/aircraft structures [27,28], robot manipulators [29], vibration controls and isolations, high-precision devices, microsensors/actuators, thin-film MEMS [30], health monitoring [31], microdisplacement actuation and control [25], and so on. Additional applications in smart structures and structronic systems encompass distributed structural control [16,[32][33][34][35][36], rotor dynamics control [37], self-sensing actuators [38][39][40], orthogonal modal sensors/actuators [41][42][43], space truss members [44], noise control [45], vibration isolators [46], active constrained damping [47], morphing of wings and blades [48], microscopic neural-sensing and actuation characteristics of conical, paraboloidal, toroidal and spherical structronic shells [49][50][51][52][53][54][55], and so on.…”
Section: Piezoelectric Materialsmentioning
confidence: 99%
“…Accelerometers have been commonly used to measure real-time acceleration of structures caused by vibration [Peeters et al 2001;Hong et al 2002;Kim and Melhem 2004;Lin et al 2005]. There is also extensive work in the literature which considers the use of PZTs to monitor vibration [Banks et al 1996;Jian et al 1997;Soh et al 2000;Winston et al 2001;Fukunaga et al 2002;Giurgiutiu et al 2002]. Among conventional sensors in SHM, PZTs have the advantages of being small, light, inexpensive, and self-excited with the further benefits of having a high signal to noise ratios and being easily integrated into structures.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental and theoretical studies of damage detection through modal analysis have been reported. Representative examples include Adams et al [1], Cawley and Adams [2], Armon et al [3], Swamidas and Chen [4], Papadopoulos and Garcia [5], and Jian et al [6]. Common vibration-based damage metrics measure changes in modal parameters, such as natural frequencies, mode shapes or mode shape curvature or some combination of frequency and mode shape information.…”
Section: Introductionmentioning
confidence: 99%